ENHANCING FOOD SECURITY THROUGH EDUCATION ON ANIMAL PROTEIN IN KARANGJENGKOL VILLAGE PURBALINGGA DISTRICT - Rachmah, Malinda; Budiyoko, Budiyoko; Zulkifli, Lutfi; Sunendar, Sunendar (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Food insecurity is a condition of inadequate food and nutrition experienced by people in certain areas, which has an impact on the inhibition of physiological growth and public health. Generally, food insecurity occurs in villages that are far from urban access, even though the natural potential in villages is greater than in cities. This is also experienced by the people of KarangJengkol Village, Purbalingga Regency, Central Java. Karangjengkol Village has great natural potential due to its location on the slopes of Mount Slamet, but many of its people live below the poverty line, resulting in food insecurity. The real form of effort to improve the food security of the Karangjengkol Village community is to provide education about the importance of animal protein consumption. Professional rabbit farming was chosen because rabbit meat contains animal protein which is quite high compared to other meats. In addition, the temperature of Karangjengkol Village is suitable for rabbit farming. This service activity is carried out through four stages, namely 1) planning, 2) implementation, 3) evaluation, and 4) independent sustainability. Overall, this service activity went well and smoothly. The data from the results of this service activity show that 68.18% of the Karangjengkol Village community has a monthly expenditure allocation below Rp. 600,000 per person, which means that the fulfillment of animal protein tends to be low. Therefore, after this activity, it is hoped that the Karangjengkol Village community will be able to improve food security and economy through rabbit farming independently, professionally, and sustainably.